Identity and Territorial Character Re-Interpreting Local-Spatial Development - Varios autores (Desarrollo Territorial, 2014)
"In economic crisis times it seems territory «does not matter»... less than never. This argument neglects, consciously or not, the possibility of new innovative ways that precisely contribute to promoting, again, development; this time supported on cooperation and territorial intelligence for both cohesion and better quality of life from local to supra-national (EU) levels. A renewed understanding of local (territorial) development is presented in this book; a new model of competitiveness based on specific resources instead common or banal ones. The goal of this volume is re-inventing territories and exploring possibilities of vectors such identity, culture and new territorial government/governance practices.@En tiempos de crisis económicas parece que el territorio «no importa»... o importa menos que nunca. Este argumento deja de lado, conscientemente o no, la posibilidad de las nuevas formas innovadoras que contribuyen precisamente a la nueva promoción del desarrollo; en esta ocasión apoyada en la cooperación y la inteligencia territorial tanto para la cohesión como para una mejor calidad de vida a nivel local y supra-nacional, a nivel europeo. El libro recoge una comprensión renovada del desarrollo local (territorial); un nuevo modelo de competitividad basado en recursos específicos en lugar de en recursos comunes y banales. El objetivo del volumen es reinventar los territorios y explorar las posibilidades de vectores como la identidad, la cultura y las nuevas prácticas territoriales de gobierno/gobernanza."